Evaluation of the diagnostic accuracy of prototype rapid tests for human African trypanosomiasis. - Jeremy M Sternberg; Marek Gierliński; Sylvain Biéler; Michael A J Ferguson; Joseph M Ndung'u (Public Library of Science (PLoS), 2014)
Diagnosis of human African trypanosomiasis (HAT) remains a challenge both for active screening, which is critical in control of the disease, and in the point-of-care scenario where early and accurate diagnosis is essential. Recently, the first field deployment of a lateral flow rapid diagnostic test (RDT) for HAT, "SD BIOLINE HAT" has taken place. In this study, we evaluated the performance of "SD BIOLINE HAT" and two new prototype RDTs.The performance of "SD BIOLINE HAT" and 2 prototype RDTs was tested using archived plasma from 250 Trypanosoma brucei gambiense patients, and 250 endemic controls. As well as comparison of the sensitivity and specificity of each device, the performance of individual antigens was assessed and the hypothetical performance of novel antigen combinations extrapolated. Neither of the prototype devices were inferior in sensitivity or specificity to "SD BIOLINE HAT" (sensitivity 0.82±0.01, specificity 0.97±0.01, 95% CI) at the 5% margins, while one of the devices (BBI) had significantly superior sensitivity (0.88±0.03). Analysis of the performance of individual antigens was used to model new antigen combinations to be explored in development of the next generation of HAT RDTs. The modelling showed that an RDT using two recombinant antigens (rLiTat1.5 and rISG65) would give a performance similar to the best devices in this study, and would also offer the most robust performance under deteriorating field conditions.Both "SD BIOLINE HAT" and the prototype devices performed comparably well to one another and also to the published performance range of the card agglutination test for trypanosomiasis in sensitivity and specificity. The performance of individual antigens enabled us to predict that an all-recombinant antigen RDT can be developed with an accuracy equivalent to " SD BIOLINE HAT." Such an RDT would have advantages in simplified manufacture, lower unit cost and assured reproducibility.